Effects of acid fog and detergents on foliar leaching of cations - Paoletti, E; GELLINI, R; Barbolani, E (Water, Air, & Soil Pollution, 1989)
Relative rates of nutrient leaching from the epygeous apparatus of Quercus ilex L., Fagus sylvatica L., Acer opalus Mill., Euonymus japonicus L. and Phaseolus vulgaris L. were examined after exposure to simulated acid fog. Copper, A1, Fe, Mn, Ca, Mg, and Pb were preferentially leached at low pH, whereas leaching rates of Na, K, and Cd did not appear to be pH-influenced. Addition of surfactant to the spray solutions showed a slight reduction of leaching for all elements investigated. Except for Mg, foliar nutrient levels were not influenced during our experiments.
Keywords: acid deposition; detergent (voyant); nutrient leaching

Elemental leaching from Quercus ilex L. in response to simulated acidic fog - Paoletti, E; Udisti, R; Pantani, F; Barbolani, E (Water, Air, & Soil Pollution, 1989)
Quercus ilex L. seedlings were intermittently exposed to simulated acidic and non-acidic fogs in 6-hr events for 16 times. After a 1-mo break, treatments were carried out again for a 5 day period. Strong acidity neutralization, weak acidity release and cation leaching from foliage and stem were determined. Leaching of AI, Cu, Mn, Fe, Cd, Pb, Ca, Mg, and K increased in response to acid treatment. This effect was less marked for Na. A positive correlation between H ÷ uptake and cation leaching was found. Cationic release and neutralization of strong acidity increased after breaks in acid treatment, but this faculty and the a m o u n t of leached cations and neutralized acidity decreased with time. The stem showed a higher cation loss and higher buffer capacity than the leaves.
Keywords: acidity; Cations (voyant); foliar leaching